Speech Error Made By Bertie, The Main Character, In The King's Speech Movie - Muniroh, Zuchriyanti; , Prof. Dr. Endang Fauziati M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This is descriptive qualitative research. It aims to describe the types of speech errors made by Bertie, to describe the frequency of speech errors made by Bertie, to describe the dominant speech error found in the conversation made by Bertie, to reveal the source of error appear by Bertie, and to describe the pedagogical implication in The King's Speech movie. In collecting data, the writer uses documentation by noting and coding the data which contain speech errors in The King's Speech movie. The researcher analyzes the data based on psycholinguistic approach. From the data analysis, the researcher finds all types of speech error based on the theory of Clark and Clark and Jean Aitchison. From the data analysis, the researcher finds nine types of speech errors, namely: silent pause, filled pause, retraced false start, unretraced false start, corrections, interjections, repeats, stutters, and slip of the tongue. From 130 data the researcher finds nine speech errors, there are (1) silent pauses (52 or 40%), (2) filled pauses (4 or 3,08%), (3) repeats (34 or 26,15%), (4) unretraced false stars (5 or 3,85%), (5) retraced false stars (1 or 0,78%), (6) corrections (3 or 2,30%), (7) interjection (3 or 2,30%), (8) stutters(27 or 20,78%), and (9) slips of the tongue (1 or 0,78%). In the mean time, the researcher finds some sources that cause speech errors. There are cognitive, psychological, and social reasons. There are many speech errors committed by Bertie in The King's Speech movie which caused by certain aspects. It means that speech error is commonly committed by people either native or nonnative speakers.